Dochody podatkowe w budżetach jednostek samorządu terytorialnego a zasada samodzielności finansowej - Dziuba, Jarosław (Tax revenues in the budgets of local authority units vs. the principle of financial independence, 2007)
The financial independence of local authorities becomes one of their basic rules. Considering its revenue aspect it results mainly from the scope of their authority to influence tax revenues by due bodies representing the commune, which in theory and practice are considered as basic sources of local authority units financing. These rights may refer, among others, to the construction of tax elements (so called tax technique) which is connected with the notion of tax authority. Taxes which constitute the source of commune revenues are not a homogenous category from this point of view. The objective of the hereby article is to define legal options of influencing these particular types of revenues by local authorities, as well as the analysis of their construction, mainly from the point of view of implementing, by communes, the instruments of tax authority which are available to them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 26-40